2010
DOI: 10.1007/s12272-010-0313-3
|View full text |Cite
|
Sign up to set email alerts
|

Selective inhibition of activated stellate cells and protection from carbon tetrachloride-induced liver injury in rats by a new PPARγ agonist KR62776

Abstract: Activated hepatic stellate cells (HSC) are the primary source of extracellular matrix proteins found in liver fibrosis/cirrhosis patients. Therefore, the prevention of HSC activation is an important strategy for treating severe liver injury. This study examined the effects of KR62776, a new peroxisome proliferator-activated receptor γ (PPARγ) agonist, on the rate of cell proliferation and expression of α-smooth muscle actin (α-SMA) in rat hepatic stellate HSC-T6 cells. In addition, its effects on the liver dam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 34 publications
1
15
0
2
Order By: Relevance
“…Additionally, more advanced fibrosis was seen in MCD-fed Gadd45a -null mice compared with the similarly-treated WT counterparts. These findings are consistent with a previous report that treatment with a peroxisome proliferator-activated receptor gamma agonist KR62776 suppresses stellate cell activation through Gadd45α induction and attenuates carbon tetrachloride-induced liver fibrosis in rats [25]. Additionally, a recent study revealed that knockdown of Gadd45α in isolated hepatic stellate cells enhanced carbon tetrachloride-induced ROS production [26].…”
Section: Discussionsupporting
confidence: 92%
“…Additionally, more advanced fibrosis was seen in MCD-fed Gadd45a -null mice compared with the similarly-treated WT counterparts. These findings are consistent with a previous report that treatment with a peroxisome proliferator-activated receptor gamma agonist KR62776 suppresses stellate cell activation through Gadd45α induction and attenuates carbon tetrachloride-induced liver fibrosis in rats [25]. Additionally, a recent study revealed that knockdown of Gadd45α in isolated hepatic stellate cells enhanced carbon tetrachloride-induced ROS production [26].…”
Section: Discussionsupporting
confidence: 92%
“…Thus, increasing PPARG expression levels in HSCs should be an effective means of liver fibrosis prevention ( Galli et al, 2000 , 2002 ; Xu et al, 2003 ). Furthermore, some PPARG agonists, such as troglitazone, thiazolidinediones, saroglitazar, KR62776, GW7845, 6-octadecynoic acid, and 15d-PGJ2, have been proven to attenuate liver fibrosis by cell-based or animal experiments ( Marra et al, 2000 ; Galli et al, 2002 ; Zhao C. et al, 2006 ; Bae et al, 2010 ; Ohtera et al, 2013 ; Jain et al, 2017 ). PPARG agonists can therefore be concluded to be effective treatments for liver fibrosis by inhibiting the HSC activation; and PPARG is a promising therapeutic target for antifibrotic chemotherapy ( Zhang F. et al, 2013 ).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, activated HSCs are able to upregulate the expression of cytoskeletal proteins, including α-SMA. Therefore, α-SMA is considered a marker of HSC activation, which may reflect the degree of liver fibrosis ( 25 , 26 ). Alterations to the hepatic architecture occur due to the combined increase in cytoskeletal protein synthesis and the inability to break down these proteins, resulting in liver fibrosis and, eventually, cirrhosis ( 27 ).…”
Section: Discussionmentioning
confidence: 99%